2021
DOI: 10.2298/tsci191115148s
|View full text |Cite
|
Sign up to set email alerts
|

Application of automatic control furnace for combustion of biomass briquette fuel for tobacco curing

Abstract: Applying biomass energy for curing flue-cured/Virginia tobacco heating is the best way to realize green tobacco production. Aiming to satisfy the heating demand for flue-cured tobacco curing, a new heating device that uses biomass briquettes as fuel for curing tobacco is adopted the first time, which was developed using modern mature electromechanical and computer technology. The new device consists of automatic feeding, ash cleaning, ventilation, and ignition systems governed by an intelligent tobacco-curing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…As compared to firewood and the same direct-fired combustion mode, BBF burned more stably mainly due to its uniform size; the upgraded energy efficiency for burning BBF ranged from 39 to 42% [34]. With burning gasification gas applying the special furnace structure for BBF via manual operation [26,35], the energy efficiency could be improved from 53.17 to 55.26%. In this work, applying mature electromechanical and computer technology with integrated combustion/gasification furnace for BBF, the system thermal efficiency is improved to 56.93%.…”
Section: Comparison Between Conventional and Biomass Curing Techniquesmentioning
confidence: 99%
“…As compared to firewood and the same direct-fired combustion mode, BBF burned more stably mainly due to its uniform size; the upgraded energy efficiency for burning BBF ranged from 39 to 42% [34]. With burning gasification gas applying the special furnace structure for BBF via manual operation [26,35], the energy efficiency could be improved from 53.17 to 55.26%. In this work, applying mature electromechanical and computer technology with integrated combustion/gasification furnace for BBF, the system thermal efficiency is improved to 56.93%.…”
Section: Comparison Between Conventional and Biomass Curing Techniquesmentioning
confidence: 99%
“…In order to reduce deforestation, tobacco drying systems that do not use wood are researched and manufactured for use. These drying systems have a forced air circulation system and automatic control system to save energy and reduce labour [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Bypassing the use of coal-fired heating for flue-cured tobacco curing can effectively ameliorate the current global environmental pollution problem [1]. With technological advances increasing the use of combustion technology using BPF burners for flue-cured tobacco heating (FTH), a growing number of flue-cured-tobacco-producing countries and regions have begun to transition from fossil fuels to biomass fuel as their primary tobacco-curing heat source [2,3]. Through the analysis of various heat sources in the agricultural field of flue-cured tobacco production, previous studies have indicated that BPT offers an optimal method to realize the green production of flue-cured tobacco [4][5][6].…”
Section: Introductionmentioning
confidence: 99%